Case Report: Longitudinal monitoring of clonal evolution by circulating tumor DNA for resistance to anti-EGFR antibody in a case of metastatic colorectal cancer - Sagawa, Tamotsu; Sato, Yasushi; Hirakawa, Masahiro; Hamaguchi, Kyoko; Tamura, Fumito; Nagashima, Hiroyuki; Fujikawa, Koshi; Okamoto, Koichi; Kawano, Yutaka; Sogabe, Masahiro; Miyamoto, Hiroshi; Takayama, Tetsuji (Frontiers in Oncology, 2023)
Background: Treatment with anti-EGFR antibody has been shown to prolong survival in patients with RAS wild-type metastatic colorectal cancer (mCRC). However, even patients who initially respond to anti-EGFR antibody therapy, almost without exception, develop resistance to the therapy and then fail to respond. Secondary mutations in the mitogen-activated protein (MAPK) signaling pathway (mainly in NRAS and BRAF) have been implicated in anti-EGFR resistance. However, the process by which resistant clones develop during therapy has not been elucidated, and considerable intrapatient and interpatient heterogeneity exists. Circulating tumor DNA (ctDNA) testing has recently allowed the noninvasive detection of heterogeneous molecular alterations that underlie the evolution of resistance to anti-EGFR. In this report, we describe our observation of genomic alterations in KRAS and NRAS in a patient with acquired resistance to anti-EGFR antibody drugs by tracking clonal evolution using serial ctDNA anaylsis. Case presentation: A 54-year-old woman was initially diagnosed with sigmoid colon cancer with multiple liver metastases. After receiving first-line mFOLFOX + cetuximab, second-line FOLFIRI + ramucirumab, third-line trifluridine/tipiracil + bevacizumab, fourth-line regorafenib, and fifth-line CAPOX + bevacizumab, she was rechallenged with CPT-11 + cetuximab. The best response to anti-EGFR rechallenge therapy was a partial response. RAS in the ctDNA was assessed during treatment. The RAS status changed from wild type to mutant type, back to wild type, and again to mutant type (NRAS/KRAS codon 61) during the course of treatment. Conclusion: In this report, tracking of ctDNA allowed us to describe clonal evolution in a case in which we observed genomic alterations in KRAS and NRAS in a patient who acquired resistance to anti-EGFR antibody drugs during treatment. It is reasonable to consider repeat molecular interrogation during progression in patients with mCRC by using ctDNA analysis, which could help to identify patients who may benefit from a rechallenge strategy.